STRENGTHENING THE EDUCATION OF NATIONALIST CHARACTER AND INTERGRITIY THROUGH SOCIAL STUDIES EDUCATION - Widyasari, Nanda; Mutammima, Vina; Purnomo, Agus (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Good education is an education that follows the times. Every era has its own challenges and ways of dealing with it. The 21st century is a time when technology and information have developed very rapidly. These developments can be felt by all levels of society, especially learners. There is a need for education for students to meet the needs and overcome the challenges of the 21st century. Character education is the deepest dimention of indonesia education. In accordance with the 8th Nawacita on mental revolution which is manifested in the character education reinforcement movement. There are five characters, one of which is nationalist and integrity. This article was written based on research at SMPN 8 Malang. In SMPN 8 Malang there are saveral related activities with strengthening character education can be done/tucked in the process of learning activities at school,both outside the classroom and in the classroom. In the classroom can be included in each subject, one of them is social studies education. Social studies is an integrated study of social sciences and humanities aimed at realizing good citizens. Techniques used in data collection are observation and interview. The results of the findings are described in descriptive form. Techniques used in data collection are literature study, data collection, and analysis. The results of the findings are described in descriptive form.